2014
DOI: 10.1007/s00109-014-1192-8
|View full text |Cite
|
Sign up to set email alerts
|

Denbinobin upregulates miR-146a expression and attenuates IL-1β-induced upregulation of ICAM-1 and VCAM-1 expressions in osteoarthritis fibroblast-like synoviocytes

Abstract: Denbinobin inhibited IL-1β-induced ICAM-1/VCAM-1 expression and monocyte adhesion to OA-FLS. It was due to denbinobin increased miR-146a level, which in turn inhibited NF-κB signaling. Our overall findings suggest that denbinobin can be used as a potent anti-inflammatory agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…In the present study, it was shown that PDGF-BB stimulation significantly increased the levels of phosphorylated p38 MAPK and Erk1/2 in VSMCs, which was inhibited by evodiamine treatment. These findings were in accordance with previous studies involving tumor cells, and suggested that the inhibition of mitogenesis and p-38/p-Erk activity may serve as the molecular basis for the functions of evodiamine (21,27,28). However, the regulation of p38 and Erk activity by evodiamine is cell type-dependent and may be negative or positive.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, it was shown that PDGF-BB stimulation significantly increased the levels of phosphorylated p38 MAPK and Erk1/2 in VSMCs, which was inhibited by evodiamine treatment. These findings were in accordance with previous studies involving tumor cells, and suggested that the inhibition of mitogenesis and p-38/p-Erk activity may serve as the molecular basis for the functions of evodiamine (21,27,28). However, the regulation of p38 and Erk activity by evodiamine is cell type-dependent and may be negative or positive.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the observation that PDGF-BB increased and evodiamine decreased the expression of p21 in the present study was not unusual. Of note, the inhibitory effects of evodiamine on cell cycle progression have been previously observed in various human tumor cell lines, including small-cell lung cancer cells (20), gastric cancer cells (11), breast cancer cells (21), gastric adenocarcinoma cells (22) and cervical carcinoma HeLa cells (23), and are considered to be important in the antitumor action of evodiamine. The data obtained in the present study extends the current recognition of evodiamine, and suggested that the regulation of cell cycle progression by evodiamine may be general and function in a broader range of cell types, including tumor cells and vascular cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…MicroRNAs are small noncoding RNAs with lengths of 21-25 nucleotides, which regulate gene expression at the posttranscriptional level [32][33][34]. Aberrant expressions of microRNAs have been found in various types of cancers [35].…”
Section: Introductionmentioning
confidence: 99%
“…In other inflammatory diseases, miRNA-155 can also indirectly promote the production of IL-1β [33,34]. There are also several miRNAs which can indirectly inhibit the production of IL-1β, such as miR-146a miR-223, and miRNA-146b-5p [30,[35][36][37][38][39].…”
Section: Mirnas and Inflammatory Cytokinesmentioning
confidence: 99%